2002
DOI: 10.1159/000065416
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity Associated with Inflammatory Responses and Cytokine Production against Common Dietary Proteins in Patients with Autism Spectrum Disorder

Abstract: Objectives: Children with autism spectrum disorder (ASD) frequently reveal various gastrointestinal (GI) symptoms that may resolve with an elimination diet along with apparent improvement of some of the behavioral symptoms. Evidence suggests that ASD may be accompanied by aberrant (inflammatory) innate immune responses. This may predispose ASD children to sensitization to common dietary proteins (DP), leading to GI inflammation and aggravation of some behavioral symptoms. Methods: We measured IFN-γ, IL-5, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(134 citation statements)
references
References 30 publications
10
124
0
Order By: Relevance
“…Several studies have focused on immunological responses to dietary proteins, such as gluten and casein. Jyonouchi et al 57 found that peripheral blood mononuclear cells from children with ASD responded to gliadin, cow's milk protein, and soy by producing higher levels of inflammatory cytokines, compared with peripheral blood mononuclear cells from typically developing children. However, children in this study were selected on the basis of having previously seen behavior improvements on a restricted diet and may translate to a specific subgroup of ASD who have gastrointestinal (GI) symptoms.…”
Section: Autoimmunity and Immune Dysfunction In Individuals With Asdmentioning
confidence: 99%
“…Several studies have focused on immunological responses to dietary proteins, such as gluten and casein. Jyonouchi et al 57 found that peripheral blood mononuclear cells from children with ASD responded to gliadin, cow's milk protein, and soy by producing higher levels of inflammatory cytokines, compared with peripheral blood mononuclear cells from typically developing children. However, children in this study were selected on the basis of having previously seen behavior improvements on a restricted diet and may translate to a specific subgroup of ASD who have gastrointestinal (GI) symptoms.…”
Section: Autoimmunity and Immune Dysfunction In Individuals With Asdmentioning
confidence: 99%
“…It is possible that this indicates some abnormality of the gastrointestinal system, perhaps related to the immune abnormalities reported in the gastrointestinal tract in children with autism, that affects the apo. 29,31,64,65,66 Alternatively, the changes in apo could be due to differences in diet or various treatments.…”
Section: Apolipoproteinsmentioning
confidence: 99%
“…There are reports that children with ASD have abnormalities in the peripheral blood cells and cytokines that mediate both innate and adaptive responses (Connolly et al, 1999;Croonenberghs, Bosmans, Deboutte, Kenis, & Maes, 2002a;Gupta, Aggarwal, Rashanravan, & Lee, 1998;Jyonouchi, Sun, & Itokazu, 2002;Singh, 1996;Warren, Foster, & Margaretten, 1987). Within the adaptive immune response, elevated levels have been reported for both T H 1 cytokines, commonly seen in autoimmune disorders (Singh, 1996), and T H 2 cytokines, as seen in atopic diseases (Gupta, Aggarwal, & Heads, 1998).…”
Section: Pervasivementioning
confidence: 99%